Simulation of a passive solar dryer to charqui production using temperature and pressure networks. (September 2015) - Duran, G.; Condorí, M.; Altobelli, F.
Highlights: An improved passive solar dryer with chimney and wind turbine is built. The dryer is tested with charqui, improving the final quality and drying time. The simulation of the dryer is developed using electrical analogy. The simulated and measured results are compared with high regression coefficients. Abstract: This paper presents a passive solar dryer that includes a chimney and a wind turbine to improve the airflow rate. The prototype of 2 m 2 of drying chamber area was tested to obtain charqui (dried beef). In relation to the traditional charqui, the final quality was greatly improved and drying time was reduced to less than two sunny days. A simulation method of the passive solar dryer is also presented. In this, pressure and thermal coupled network are used to represent the dryer, and they are solved by electrical analogy. Simulation and experimental results were analyzed, showing a good fit to the measured data, especially with trends. In all cases, the fits between measured and simulated data have coefficients of determination r 2 higher than 0.93. The simulation method is suitable to be used in the design of passive solar dryers to find the optimum mass air flow.